The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
TRANSDUCERS 2007 - 2007 International Solid-State Sensors, Actuators and Microsystems Conference 2007
DOI: 10.1109/sensor.2007.4300575
|View full text |Cite
|
Sign up to set email alerts
|

Realtime 3D Stress Measurement in Curing Epoxy Packaging

Abstract: This paper presents a novel method to characterize stress in microsystem packaging. A circular p-type piezoresistor is implemented on a (001) silicon chip. We use the circular stress sensor to determine the packaging induced stress in a polystyrene tube filled with epoxy. The epoxy curing process is monitored by stress measurements. From the stress measurements we conclude that the epoxy cures in 8 hours at room temperature. We find the difference in in-plane normal stresses to be σ xx -σ yy =6.7 MPa and (σ xx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Richter et al [48], [153], [154] demonstrated a novel piezocoefficient-mapping device to measure 3D stresses in device packaging and also to extract directional piezoresistive coefficients (Fig. 14).…”
Section: Piezoresistance Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Richter et al [48], [153], [154] demonstrated a novel piezocoefficient-mapping device to measure 3D stresses in device packaging and also to extract directional piezoresistive coefficients (Fig. 14).…”
Section: Piezoresistance Fundamentalsmentioning
confidence: 99%
“…(b) Schematic diagram of the circular piezoresistor with a radius of 1700 μ m. From Richter et al [154], © 2007 IEEE.…”
Section: Figures and Tablesmentioning
confidence: 99%